Weekly Physical Activity Levels of Older Adults Regularly Using a Fitness Facility - Michael J. Turner; Emily E. Schmitt; Tricia Hubbard-Turner (Journal of Aging Research)
The aim of this paper was to determine if weekly physical activity levels were greater in an independent-living older adult population that was regularly participating in structured fitness activities. Also, lifetime exercise history and sex differences were investigated in an effort to understand how they relate to current weekly step activity. Total weekly step counts, measured with a pedometer, were assessed in two older adult groups; the first consisted of members of a local senior center who regularly used the fitness facility (74.5±6.0 yrs; mean ± SD) while the second group consisted of members who did not use the fitness facility (74.8±6.0 yrs). Participants also completed the Lifetime Physical Activity Questionnaire (LPAQ). No significant difference was found in the total number of weekly steps between groups (p=0.88) or sexes (p=0.27). The LPAQ suggested a significant decline in activity with aging (p=0.01) but no difference between groups (p=0.54) or sexes (p=0.80). A relationship was observed between current step activity and MET expenditure over the past year (p=0.008, r2=0.153) and from ages 35 to 50 years (p=0.037, r2=0.097). The lack of difference in weekly physical activity level between our groups suggests that independent-living older adults will seek out and perform their desired activity, in either a scheduled exercise program or other leisure-time activities. Also, the best predictor of current physical activity level in independent-living older adults was the activity performed over the past year.